2009
DOI: 10.1590/s1980-57642009dn30400008
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiovascular disease and dementia

Abstract: Longitudinal studies have shown association between cardiovascular risk factors and dementia. However, these studies are not capable of detecting asymptomatic cardiovascular alterations and thus may provide erroneous estimates of association. Autopsy studies could be more useful in elucidating these questions. The present clinicopathological study sought to examine the relationship between dementia, cardiovascular risk factors and disease.Methods603 subjects, who underwent autopsy, were classified regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Therefore, they did not contribute to the frequency of cardiovascular diseases that we report here. This is supported by the evidence derived from epidemiological studies that have previously linked cardiovascular diseases with dementia 30 and with high mortality 30 days after hip fracture. 29 On the other hand, we observed that the specific absence of heart disease contributed to a better functional state after the fracture.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, they did not contribute to the frequency of cardiovascular diseases that we report here. This is supported by the evidence derived from epidemiological studies that have previously linked cardiovascular diseases with dementia 30 and with high mortality 30 days after hip fracture. 29 On the other hand, we observed that the specific absence of heart disease contributed to a better functional state after the fracture.…”
Section: Discussionsupporting
confidence: 53%
“…The result of the research showed that cognitive deficit was associated with stroke, physical inactivity, advanced age, and low body mass index (p< 0.05) [14]. Moreover, in patients with dementia, the circle of Willis atherosclerosis was greater than in controls on univariate analysis (p=0.01).…”
Section: Resultsmentioning
confidence: 95%
“…It has been proposed that the CSVD-dementia association may be coincidental due to both conditions' prevalence in older adults. 32 Not all individuals with CSVD develop dementia, 33 implying that other factors may play a greater role. In our research, we aimed to gather clinical evidence supporting the vascular theory and clarify whether vascular pathology is a key component of dementia pathogenesis.…”
Section: Discussionmentioning
confidence: 99%